Comparison between two treatment protocols with recombinant Human Erythropoietin (rHuEpo) in the treatment of late anemia in neonates with Rh-Isoimmunization - A.A. Zuppa; G. Alighieri; A. Fracchiolla; P. Catenazzi; A. D'Antuono; R. Riccardi; M. Cavani; C. Romagnoli (PAGEPress Publications, 2012)
Objectve. The Rh-hemolytic disease can lead to a late anemia by hemolytic and hyporigenerative mechanism. We compared the effectiveness of rHuEPO in two care protocols that differ for doses of rHuEPO administrated and for timing of administration. Methods. A cohort of 14 neonates was investigated. The neonates were treated with two different protocols. Protocol A: a dose of 200 U/kg/day of rHuEpo administered subcutaneously starting from the end of the second week of life; Protocol B: a dose of 400 U/kg/day of rHuEpo administered subcutaneously starting from the end of the first week of life. Results. The hematocrit values in the protocol A group decreased during treatment (32,5% vs 25,2%), whereas the hematocrit value in protocol B group remained almost stable (38,7% vs 42,8%). The mean numbers of platelets remained stable in both groups while neutrophils increased in protocol A group and decreased in protocol B (p<0,05). Reticulocyte count increased during treatment in both groups, although only in protocol B group it was statistically significative (p<0,05). Conclusions. Our results suggest a similar efficacy between the two treatment protocols. Increasing doses of rHuEPO do not seem enhancing their effectiveness and the incidence of side effects.